Evaluation of a proposed technique to assess unscheduled DNA synthesis and genotoxicity. Issue 2 (February 1993) - Goodlad, R A; Lee, C Y; Alison, M R; Sarraf, C E; Ghatei, M A; Bloom, S R; Wright, N A
Abstract : Results from a recent, new assay suggest that omeprazole, a potent inhibitor of gastric acid secretion, is genotoxic. The principle of this assay is that the non-proliferating zone of surface gastric epithelial cells can be selectively removed by controlled digestion so that any incorporation of tritiated thymidine into these cells represents unscheduled DNA synthesis. Parietal cells (which are located below the uppermost proliferating cells) and proliferating cells in semiconservative, regular DNA synthesis could always be shown in the digested fraction, and as regular DNA synthesis takes up a thousand fold more thymidine than unscheduled DNA synthesis, any signal from unscheduled synthesis would therefore be swamped. The digestion process was also uneven, as histological analysis showed denuded patches of mucosa, and gland like structures were seen in the digest. Quantification of the number of silver grains over the nuclei showed no increase in low level labelling after omeprazole administration, indicating that there was no unscheduled DNA synthesis. The labelling index of undigested gastric tissue from omeprazole treated rats was not significantly different from that of the control group, despite an increase in the plasma gastrin value.